RESEARCH OF THE EFFECT OF DISPERSED CARBIDE FILLER ON THE TRIBOLOGICAL PROPERTIES OF COMPOSITES BASED ON PHENYLONE C-2 - Буря, Олександр Іванович; Томіна, Анна – Марія Вадимівна; Литвинова, Єлизавета Едуардівна (Problems of Friction and Wear, 2019)
It is known that wear is one of the main causes of failure of equipment of modern technics, which results in significant economic costs associated with the repair of equipment and shutdown of working process. Therefore, the subject of increasing the wear resistance details of machines and mechanisms is one of the important tasks of modern material science. One of the promising ways to increase the reliability and durability of the equipment is usage of polymer composite materials (PCM), including reinforced with dispersed fillers. The main reason of rapid development of PCM is due to the fact that traditional plastics including polyamides largely exhausted their capabilities, and modern technology progresses every year, and needs the materials with new properties, usage of that will reduce the use of scarce materials (titanium, steel, aluminium, copper and others), increase load-carrying capacity, provide significant fuel economy through weight reduction of constructions. In the article is considered the influence of titanium-tungsten-cobalt solid alloy on tribotechnical properties of composite materials based on aromatic polyamide of phenylone brand С-2. Analyzing the results of obtained researches, it is seen that adding of dispersed filler due to positive results: decrease of the intensity of linear wear and indicator of abrasive wear of phenylone to 30-90 and 22- 45%. It has been established that the optimal complex of properties has composite containing 3 wt.% of carbide. As a result, it is possible to recommend production of details with high wear resistance for cars, road and agricultural machines working in aggressive conditions, high temperatures and variable loads.